2001
DOI: 10.1046/j.1464-410x.2001.02254.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of treatments for erectile dysfunction in patients with prostate cancer after radical retropubic prostatectomy

Abstract: Objective To assess the effectiveness of a progressive local treatment protocol for erectile dysfunction (ED) in patients after undergoing radical retropubic prostatectomy (RRP) for prostate cancer. Patients and Methods The study included 85 patients (mean age 59.5 years, range 50±75) with ED after RRP. Treatment was offered in four progressive phases, with patients passing to the next phase only if they failed the previous one: in phase I patients used a vacuum erection device; in phase II, sildena®l; in phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 29 publications
(33 reference statements)
1
42
0
1
Order By: Relevance
“…[7][8][9] According to a literature review, the efficacy of sildenafil ranges from 14 to 53%, but this range can be extended to 14-85% on switching to ICI. 10,11 Penile rehabilitation should be discussed with all patients, regardless of their sexual motivation, and initiated promptly after RP. 9,12,13 Among our 63 RP patients, 74.6% were regularly using ED treatment and 81% had erections adequate for intercourse with or without pharmacological assistance.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] According to a literature review, the efficacy of sildenafil ranges from 14 to 53%, but this range can be extended to 14-85% on switching to ICI. 10,11 Penile rehabilitation should be discussed with all patients, regardless of their sexual motivation, and initiated promptly after RP. 9,12,13 Among our 63 RP patients, 74.6% were regularly using ED treatment and 81% had erections adequate for intercourse with or without pharmacological assistance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Bechara and coauthors 49 performed a prospective study which showed that the 3-drug mixture is more effective than high-dose PGE1 alone in achieving erections suitable for penetration. In addition, Baniel and colleagues 50 found that ICSI of papaverine, phentolamine and PGE1 combination was effective in 51 (85%) of 60 patients following RP using structured interviews with patients and their partners.…”
Section: Intracavernous Injections Of Vasoactive Agentsmentioning
confidence: 99%
“…This is relatively simple to use, but the erection produced is unlike a physiologic erection. Some patients consider it unappealing; in a report by Baniel et al, 31 only 11 (14%) of 78 patients who responded to the vacuum erection device agreed to continue with it. For patients who failed either sildenafil or MUSE therapy and do not want to use ICI or penile prostheses, a combination of MUSE and sildenafil may allow erections sufficient for penetration.…”
Section: Other Approachesmentioning
confidence: 99%
“…After 1 year of followup, ICI was described as the most effective alternative for ED after radical retropubic prostatectomy. 31 Kim and colleagues 42 have described some recovery of erectile function in men who underwent bilateral sural nerve graft placement during radical retropubic prostatectomy where both cavernous nerves were deliberately resected. Other authors remain skeptical about the value of nerve grafts in restoring sexual function in men undergoing radical surgery.…”
Section: Other Approachesmentioning
confidence: 99%